Evaluation of proline-rich antimicrobial peptides as potential lead structures for novel antimycotics against Cryptococcus neoformans - Brakel, Alexandra; Grochow, Thomas; Fritsche, Stefanie; Knappe, Daniel; Krizsan, Andor; Fietz, Simone A.; Alber, Gottfried; Hoffmann, Ralf; Müller, Uwe (Frontiers in Microbiology, 2024)
BACKGROUND: Cryptococcosis and cryptococcal meningitis, caused by Cryptococcus neoformans infections, lead to approximately 180,000 deaths per year, primarily in developing countries. Individuals with compromised immune systems, e.g., due to HIV infection (AIDS) or chemotherapy, are particularly vulnerable. Conventional treatment options are often limited and can cause severe side effects. Therefore, this study aimed to investigate the antifungal effect of insect-derived proline-rich antimicrobial peptides (PrAMPs) against C. neoformans. These peptides are known for their low toxicity and their high efficacy in murine infection models, making them a promising alternative for treatment.RESULTS: A preliminary screening of the minimal inhibitory concentrations (MICs) of 20 AMPs, including the well-known PrAMPs Onc112, Api137, and Chex1Arg20 as well as the cathelicidin CRAMP against the C. neoformans strains 1841, H99, and KN99α revealed promising results, with MICs as low as 1.6 µmol/L. Subsequent investigations of selected peptides, determining their influence on fungal colony-forming units, confirmed their strong activity. The antifungal activity was affected by factors such as peptide net charge and sequence, with stronger effects at higher net charges probably due to better intracellular uptake confirmed by confocal laser scanning microscopy. Inactive scrambled peptides suggest a specific intracellular target, although scanning electron microscopy showed that PrAMPs also damaged the cell exterior for a low proportion of the cells. Possible pore formation could facilitate entry into the cytosol.